Posterior Reversible Encephalopathy Syndrome in a Patient with Hemorrhagic Fever with Renal Syndrome - Ermira Muco; Amela Hasa; Arben Rroji; Arta Kushi; Edmond Puca; Dhimiter Kraja (Case Reports in Infectious Diseases, 2020)
We presently report the case of hantavirus infection in a 45-year-old male who was hospitalized to our clinic of infectious diseases, with fever, myalgia, vomiting, nausea, headache, and abdominal pain. The physical findings included hepatomegaly, splenomegaly, rash, and conjunctival injection. Eight days before the start of complaints, the patient has cut trees in the mountain. An acute renal failure was observed with an oliguria and an increase of serum creatinine and blood urea nitrogen. Urinalysis shows albuminuria and hematuria. Elevations of amylase, lipase, and liver enzymes levels, low serum albumin level, and thrombocytopenia were observed. A positive ELISA test for hantavirus IgM/IgG antibodies confirmed hemorrhagic fever with renal syndrome. On the third day of hospitalization, the patient had seizures. The unenhanced head computed tomography (CT) performed after seizures showed subcortical bilateral hypodensities within frontal, parietal, and occipital regions corresponding to areas of increased signal intensity in magnetic resonance imaging (MRI) associated with cerebral edema in posterior reversible encephalopathy syndrome (PRES). The treatment consisted of supportive therapy. The patient underwent another head MRI with contrast enhancement after 2 months, which resulted normal.